Ana (orexia): uma imagem obscena - Ribeiro, Camila Neiva de Gouvêa (2008)
Anorexia, known in the scientific community for many centuries, not only comes to arouse interest of specialists and studious on the subject, but also of the media scene and common sense. As it generates concerns in the social and familiar circle, for the proximity with death where some people put themselves, has become subject of different research. Considering these references and the dissemination of blogs number, in the Internet, that bow to anorexia and the search of a bony body like a life style , under Ana s leadership (Ana/orexia), we do in this work a study of problematical body image in anorexia, starting from analysis of female teenagers statements on Brazilians blogs, having psychoanalytical interpretation as analysis resource. We suppose that such attitudes reflect an obscene and transgressive image, illustrated for the desire that these girls have to reach a bony body, being printed the horror of death and pushing the Other to anguish. Analyzing eight blogs, starting from filed posts, regarding of period between January and December of 2006, we search to understand the identification force among pró-anas , the relation that are established between anorexia ( Ana ) and bulimia ( Mia ) and the way as they are seen themselves, when marking a particular queerness in its bodies and doing the blog a place of lusting and communication among psychical ghosts. With this study, we hope to offer subsidies for the handling in addition clinic and symptoms that take the body in consideration